COMIRNATY® (Tozinameran), COVID-19 mRNA vaccine (nucleoside modified, 10 micrograms/dose) - paediatric Pfizer-BioNTech COVID-19 vaccine : COVID-19 vaccine explainer : 03 June 2022 (World Health Oragnization, 2022)
COMIRNATY® (10 micrograms/dose), also known as paediatric Pfizer-BioNTech COVID-19 vaccine, is a messenger RNA (mRNA) based vaccine against coronavirus disease 2019 (COVID-19) for children from 5 years to 11 years of age. The mRNA instructs the cell to produce proteins of the S antigen (a piece of the spike protein unique to SARS-CoV-2) to stimulate an immune response. As COMIRNATY® does not contain the virus to produce immunity the vaccine cannot give the child COVID-19.
Keywords: veřejné zdravotnictví; pediatrie; vakcíny; preventivní medicína; COVID-19 Vaccines; vakcíny proti COVID-19; COVID-19; Vaccines